Prevalence of Anemia and its Determinants among Elderly People of Uttarakhand, India - Sumit Saxena; Puneet Gupta; Anurag Srivastava; Sonam Maheshwari (Indian Association of Preventive and Social Medicine, 2021)
Introduction: Anemia is a sign of serious disease at all ages; but in elderly population it is especially true. According to epidemiologic data, its prevalence rises with increasing age sharply after the age of 60years. Method: To evaluate the prevalence of anemia and its determinants among older age group in Uttarakhand, NFHS-IV (2015-16) data was used. For socio demographic analysis, study included 7056 individuals (After excluding missing information) aged 60 years and above. Results: The median age was 66.38years (range,60-95years). The mean levels of hemoglobin (Mean ± SD) were 14.23 ± 1.29 g/dL in men and13.75 ± 1.15 g/dL in women, and the overall prevalence of anemia was 36.42% (2502/6870):In men the prevalence was 36.86 % (2096/5687) and 34.32% (406/1183)in Women. The Prevalence in age group 60-69, 70-79 and ≥80 was 35.2%, 38.1% and 41.2% respectively. It was found that the prevalence of anemia differed significantly between those of age 60-69 and 70-79 years, those of age 60-69 and ≥80 years, and those of age 70-79 years and ≥80 years.Conclusions: The prevalence of anemia among elderly people of Uttarakhand was determined to be 35.9% and it increased with age. Male sex, older age, low BMI, low education and nuclear family were identified as independent risk factors of anemia among the elderly Indians.